2007
DOI: 10.1007/s11136-007-9205-5
|View full text |Cite
|
Sign up to set email alerts
|

Life satisfaction decreases during adolescence

Abstract: Decreasing life satisfaction has to be considered as a developmental phenomenon. Associations with the increasing prevalence of depression and suicidal ideation during adolescence are discussed. Life satisfaction should be considered a relevant aspect of adolescent's well-being and functioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

46
277
11
40

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 364 publications
(374 citation statements)
references
References 33 publications
46
277
11
40
Order By: Relevance
“…These findings indicate that healthy individuals experience changes in their expectations and in the feeling of well-being along life, and adolescents are less happy with their family relationships than children (20) . Palermo et al (21) reported a greater commitment with physical health among adolescents with SCD than among children when they evaluated HRQL of children and adolescents according to their parent.…”
Section: Discussionmentioning
confidence: 87%
“…These findings indicate that healthy individuals experience changes in their expectations and in the feeling of well-being along life, and adolescents are less happy with their family relationships than children (20) . Palermo et al (21) reported a greater commitment with physical health among adolescents with SCD than among children when they evaluated HRQL of children and adolescents according to their parent.…”
Section: Discussionmentioning
confidence: 87%
“…The small age effect indicating a linear decreasing trend in global LS from ages 10 to Henrich (2007). Another limitation of study two is the cross-sectional design, therefore, the trend of decreasing LS needs to be replicated using a longitudinal design to more systematically evaluate age-related (vs. cohort) effects.…”
Section: Discussionmentioning
confidence: 99%
“…Everyday hassles may induce higher stress levels than before (Stroud et al, 2009), and the number of potentially stressful life events increases (Garber, Keiley, & Martin, 2002). Consequently, negative psychological outcomes, such as depression, increase (Angold, Costello, & Worthman, 1998), whereas positive psychological outcomes, such as life satisfaction (Goldbeck, Schmitz, Besier, Herschbach, & Henrich, 2007) and self-esteem (Robins & Trzesniewski, 2005), decrease over the course of adolescence. The school transition from primary to secondary school is also often accompanied by a temporary decline in general and school-related self-esteem (e.g., Watt, 2004;Zimmerman, Copeland, Shope, & Dielman, 1997).…”
Section: Building a Conceptual Frameworkmentioning
confidence: 99%